Механические размерные эффекты двухфазных неорганических материалов - Мовчан, Б.А. (Автоматическая сварка, 2008)
Extremums of strength, ductility and hardness of two-phase metallic and non-metallic materials containing nano- and microsized phases were established experimentally. It is shown that the ductility maximum, minimums of strength and hardness are characteristic of materials under the condition of equality of mean grain size D and mean free distance (mean free path) between the second phase particles Λ, i.e. at D = Λ. Maximums of strength and hardness are achieved when the mean free path Λ is equal to the mean distance between particles λ, i.e. Λ = λ. In microlaminate materials the dimensional effects are manifested at values of alternating layer thickness below 1...2 μm. An interrelation is established between the specific surface of the interphases and extreme values of mechanical properties of two-phase materials.